Application of coagulation-ultrafiltration hybrid process for drinking water treatment: Optimization of operating conditions using experimental design - Zularisam, A. W.; Salim, Mohd. Razman; Ismail, Ahmad Fauzi; Sakinah, Mimi; Matsuura, T. (Elsevier Science B.V., 2009)
Coagulation application prior to ultrafiltration process was carried out to increase NOM removal and membrane permeability. A systematic experimental design based on first order model of 24 full factorial design was used as an initial screening process to determine the significant variable factors and their inter-relationship towards natural organic matter (NOM) removal efficiency. The factors considered were SUVA (specific UV254 nm absorbance), FRT (flocculation retention time), alum dosage and pH. Statistical analysis of result has shown the main effect of alum, pH, SUVA and the two level interactions of alum and FRT, alum and SUVA, alum and pH, FRT and SUVA, and SUVA and pH were the significant model terms. Thereafter a second order model which was the 23 central composite designs (CCD) was further employed to develop a mathematical correlation model between the significant factors for the optimum modes of operating condition, with respect to NOM removal and membrane permeability. The alum dosage is found to be the most significant factor that influences the NOM removal and this is followed by the two level interactions of pH and SUVA, the main effect of pH, the main effect of SUVA, the two level interaction of SUVA and alum, the second order effect of SUVA and the second order effect of pH. In the case of membrane permeability, the main effect of alum dosage and the second order effect of pH provided the principal effect, whereas the second order effect of alum, the main effect of pH, the two level interaction of pH and SUVA, the two level interaction of SUVA and alum dose, and the main effect of SUVA provided the secondary effect. The optimized values of 5.48, 3.24 L/(m mg) and 3.0 mg Al/L of pH, SUVA and alum dose were obtained respectively, and with these proposed optimized conditions, a NOM removal of 81.28% and permeability of 30.61 LMHBar was predicted. Thereafter via experimental validation process, 79.50% and 31.29 LMHBar of NOM removal and permeability was attained, respectively. In conjuction treatment efficiency has shown excellent water quality that is well beyond the Malaysian and WHO drinking water quality regulations with > 96% colour removal, about 87% UV254 removal, < 0.2 NTU, > 99% suspended solids removal. and > 99% of turbidity removal.